2020
DOI: 10.3390/cmd1010007
|View full text |Cite
|
Sign up to set email alerts
|

The Corrosion Performance and Mechanical Properties of Mg-Zn Based Alloys—A Review

Abstract: Magnesium alloys have shown great potential for applications as both structural and biomedical materials due to their high strength-to-weight ratio and good biodegradability and biocompatibility, respectively. Among them, Mg-Zn based alloys are attracting increasing interest for both applications. As such, this article provides a review of the corrosion performance and mechanical properties of Mg-Zn based alloys, including the influence of environment and processing on both of them. The strategies for tailorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 322 publications
(352 reference statements)
2
9
0
Order By: Relevance
“…The biocompatibility of the Mg-Zn-Ca alloy found in earlier studies [50,51] was confirmed by our results. We have shown that ECAP-induced changes in the microstructure did not worsen such biocompatibility parameters as induced hemolysis and cytotoxicity against blood cells.…”
Section: Discussionsupporting
confidence: 92%
“…The biocompatibility of the Mg-Zn-Ca alloy found in earlier studies [50,51] was confirmed by our results. We have shown that ECAP-induced changes in the microstructure did not worsen such biocompatibility parameters as induced hemolysis and cytotoxicity against blood cells.…”
Section: Discussionsupporting
confidence: 92%
“…Coloured substances and pH-dependent dyes are generally included for visual monitoring of any pH changes [ 20 , 48 ]. The pH findings in our study were consistent with the Mg sample corrosion measurements, which showed that high corrosion rates dramatically increased the pH [ 49 , 50 ]. The connection between spectra and actual pH levels was evaluated using PLS modelling, as shown in Figure 5 .…”
Section: Discussionsupporting
confidence: 90%
“…The latter causes an increase in pH (over 7.8), and alkalization poisoning would induce toxicity [ 18 ]. There are several studies that investigated the effect of alloy design on corrosion control, including the use of calcium (Ca) [ [19] , [20] , [21] ], zinc (Zn) [ [22] , [23] , [24] ], gadolinium Gd [ [25] , [26] , [27] ], manganese (Mn) [ [28] , [29] , [30] , [31] ], strontium (Sr) [ 30 , 31 ], lithium (Li) [ 32 , 33 ], yttrium (Y) [ [34] , [35] , [36] , [37] ], and zirconium (Zr) [ 37 , 38 ]. It should be noted that the amount of second phase formation and its distribution and microstructural evolution can significantly influence the corrosion rate of Mg alloys [ 39 ].…”
Section: Introductionmentioning
confidence: 99%